Phospho-relay feedback loops control egress vs. intracellular development in Toxoplasma gondii - Ja E. Claywell; Yong Fu; L. David Sibley (Cell Reports)
Summary: The intracellular parasite Toxoplasma gondii alternates between a motile invasive and a quiescent intracellular replicative form, yet how these transitions are regulated is unknown. A positive feedback loop involving protein kinase G (PKG) and calcium-dependent PKs (CDPKs) controls motility, invasion, and egress by Toxoplasma gondii, while PKA isoform c1 (PKAc1) counteracts this pathway. Shortly after invasion, PKAc1 is activated by cyclic AMP (cAMP) produced by adenylate cyclases, leading to the suppression of the PKG/CDPK pathway. PKAc1 further activates phosphodiesterase 2, which selectively consumes cAMP, thus forming a negative feedback loop, causing transient activation of PKAc1. Perturbation of cyclic GMP (cGMP) vs. calcium demonstrates that PKAc1 acts on targets between guanylate cyclase and calcium release. The combined activation of PKG/CDPKs and inhibition by PKAc1, controlled by a transient negative feedback loop, ensures that the parasite is responsive to environmental signals needed to activate motility while also ensuring periods of long-term stable intracellular growth.